Nurses and allied professionals’ engagement in clinical research-in-practice: a statement of the Association of Cardiovascular Nursing & Allied Professions of the European Society of Cardiology - Fredericks, Suzanne (2025)
Many nurses and allied professionals (NAPs) lack the skills, knowledge and confidence to engage in conducting and implementing research. This statement describes the importance of NAPs' involvement in clinical research within the context of cardiovascular care. The existing gaps, barriers and enablers to NAPs involvement in research as a potential response to workforce issues in these professions as well as to contribute to excellence in patient care delivery and associated outcomes are identified. Specifically, career development pathways for NAPs are discussed. Finally, potential future directions for NAP research in clinical practice are provided.